The Role of Women in the Informal Sector Tongketongke Village, East Sinjai District, Sinjai Regency - Abdul Rahman (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
In the rural economic system, earning a living is not solely the responsibility of men as fathers and husbands; women, as mothers and wives, also play a crucial role. This is evident in Tongketongke Village. This study aims to analyze women's livelihood activities. The methods used in this study were observation and interviews. The results indicate that women's involvement in earning a living in Tongketongke Village significantly impacts household well-being. This income can be used to meet household economic needs, children's school needs, and health needs. Therefore, the income earned by women cannot be categorized as secondary income, but rather serves as a safety valve when their husbands are unemployed, given that their work is irregular or seasonal. In carrying out their activities as breadwinners, women do not neglect their duties as wives and mothers; they continue to fulfill their domestic roles before assuming their public roles